Limbic-Brainstem Roles in Perception, Cognition, Emotion and Behavior - Robert Rafal (Frontiers Research Topics, 2018)
The brainstem-limbic regions, including the superior colliculus, pulvinar and amygdala, receive direct perceptual information as a rapid, coarse, subcortical sensory system bypassing early sensory cortical systems, and play a central role in innate behaviors, including motivated and avoidance behaviors. Recent human neuropsychological studies including those on cortical blindness suggest that these subcortical sensory pathways are functional in the intact human brain and interact with more evolutionary recent cortical systems. This eBook presents up-to-date advancements in this area and to highlight the functions of the brainstem-limbic regions in a variety of perceptual, cognitive, affective and behavioral domains. We hope that this current Research Topic provides a comprehensive review to understand roles of the subcortical brainstem-limbic regions in some forms of sensory-motor coupling, cognitive and affective functions.